2011
DOI: 10.2337/db10-1338
|View full text |Cite
|
Sign up to set email alerts
|

Diet-Induced Adipose Tissue Inflammation and Liver Steatosis Are Prevented by DPP-4 Inhibition in Diabetic Mice

Abstract: OBJECTIVEDiet composition alters the metabolic states of adipocytes and hepatocytes in diabetes. The effects of dipeptidyl peptidase-4 (DPP-4) inhibition on adipose tissue inflammation and fatty liver have been obscure. We investigated the extrapancreatic effects of DPP-4 inhibition on visceral fat and the liver.RESEARCH DESIGN AND METHODSWe investigated diet-induced metabolic changes in β-cell–specific glucokinase haploinsufficient (Gck+/−) diabetic mice. We challenged animals with a diet containing a combina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
189
1
3

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 239 publications
(204 citation statements)
references
References 49 publications
11
189
1
3
Order By: Relevance
“…Trials of weight loss improve liver function and liver histology in NAFLD (28). The improvement of liver histology by sitagliptin may originate from both weight-independent and weight-dependent effects (29,30).…”
Section: Discussionmentioning
confidence: 99%
“…Trials of weight loss improve liver function and liver histology in NAFLD (28). The improvement of liver histology by sitagliptin may originate from both weight-independent and weight-dependent effects (29,30).…”
Section: Discussionmentioning
confidence: 99%
“…Limited animal studies have also suggested that DPP-4 inhibition may reduce the number of inflammatory cells within visceral adipose tissue and halt the progression of atherosclerosis via immunomodulation. [20][21][22] …”
Section: Cardiovascular Effects Of Dpp-4 Inhibitionmentioning
confidence: 99%
“…To measure adipocyte area (46), formalin-fixed, paraffin-embedded adipose tissue sections were stained with H & E, and stained images of 100 adipocytes in the adipose tissue of each mouse were used for quantitative evaluation by microscopy. Immunostaining of F4/80, a marker of tissue macrophages, was carried out for adipose tissue (45). Briefly, after endogenous peroxidase activity was blocked, deparaffinized adipose sections were incubated with the primary antibody rat monoclonal anti-mouse F4/80 antibody (4.0 g/ml) A: experimental protocol.…”
Section: Histological Analysis Of Liver and White Adipose Tissuementioning
confidence: 99%